International encyclopedia of organization studies - Clegg, Stewart; Bailey, James Russell 1963- (Gale virtual reference library, 2008)
Offers a comprehensive overview of many of the major ideas, concepts, terms, and approaches that characterize this diverse field of organization studies. Illustrates the fluidity, dynamism, and innovation that now occur in organization studies-internationally. Examines how organizations are devices for structuring life and lives are structured by organizations.